1998
DOI: 10.1183/09031936.98.12061334
|View full text |Cite
|
Sign up to set email alerts
|

Selective phosphodiesterase inhibitors modulate the activity of alveolar macrophages from sensitized guinea-pigs

Abstract: The cyclic nucleotides cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) are important second messengers in cell function. The concentration of intracellular cAMP increases either as a consequence of receptor-triggered adenylyl cyclase activation or by decreased activity of phosphodiesterase (PDE), which regulates the breakdown of cAMP and cGMP. PDE are a growing group of enzymes, classified into seven distinct families (PDE1-PDE7) with several subtypes and splice variants (for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In this regard, w e observe d that the c ombination of milrinone and the sele ctive PDE4 inhibitors, rolipram or Ro 20 -1724 had a signific ant inhibitory effe ct on arachidonate re le ase. 9 We rec ently proposed that the reduced activity of alve olar macrophage s may be involved in the inhibition of the de ve lopme nt of airw ay hype rresponsiveness by both PDE3 and PDE4 inhibitors and suggest that activation of alveolar macrophage s is a ke y e vent in the bronchopulmonary alterations that follow antige n challenge.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this regard, w e observe d that the c ombination of milrinone and the sele ctive PDE4 inhibitors, rolipram or Ro 20 -1724 had a signific ant inhibitory effe ct on arachidonate re le ase. 9 We rec ently proposed that the reduced activity of alve olar macrophage s may be involved in the inhibition of the de ve lopme nt of airw ay hype rresponsiveness by both PDE3 and PDE4 inhibitors and suggest that activation of alveolar macrophage s is a ke y e vent in the bronchopulmonary alterations that follow antige n challenge.…”
Section: Discussionmentioning
confidence: 91%
“…9 ,17 ,1 8 We have also reported that mac rophages recove red in the BAL fluid of e ithe r saline-ex posed or OA-challenge d se nsitized guinea-pigs ex hibit a PDE type 3 and a PDE type 4 is oe nzyme activity. 9 It c an there fore be suggeste d that the p rofile of PDE activities in mac rophage s may influe nce the ac tivity of PDE inhibitors. In this regard, w e observe d that the c ombination of milrinone and the sele ctive PDE4 inhibitors, rolipram or Ro 20 -1724 had a signific ant inhibitory effe ct on arachidonate re le ase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that PDE3 and PDE4 are the primary isoforms expressed in AMs [16]; therefore, we chose to examine the relative gene expression of each of these enzymes in AMs from young (day 7 and 14) compared to adult AMs (Figure 3B). There was no difference in the expression of PDE4A, PDE4B, or PDE4D between the young and the adult AMs (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Among these enzymes, phosphodiesterase type 4 (PDE4) is a high-affinity cAMP-selective isozyme (Beavo, 1995). The inhibition of PDE4 relaxes airway smooth muscle (Torphy et al, 1988;Harris et al, 1989;Shahid et al, 1991;Heaslip et al, 1994) and induces anti-inflammatory effects, such as the reduction of chemical mediator released from mast cells (Weston et al, 1997), basophils (Peachell et al, 1992;Weston et al, 1997), eosinophils (Dent et al, 1991;Underwood et al, 1993Underwood et al, , 1994Raeburn et al, 1994) and macrophages (Germain et al, 1998;Goncalves de Moraes et al, 1998). As a result, PDE4 inhibitors 668 D. Tenmizu et al ORIGINAL RESEARCH In vivo and in vitro metabolism studies demonstrated that YM-64227 is biotransformed into five hydroxylated metabolites which also inhibit PDE4 activities.…”
Section: Introductionmentioning
confidence: 99%